2003
DOI: 10.1046/j.1365-2990.2003.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of precerebellar nuclei in multiple system atrophy

Abstract: In this semiquantitative study based on 26 post-mortem cases, we describe the involvement of precerebellar nuclei in multiple system atrophy (MSA), a progressive degenerative disorder of the human central nervous system characterized by abnormal, argyrophilic and alpha-synuclein immunopositive intracellular inclusions within selectively vulnerable oligodendrocytes and nerve cells. The Campbell-Switzer silver-pyridine technique with alpha-synuclein immunoreactions using 100-microm thick sections is recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 78 publications
(88 reference statements)
2
90
0
1
Order By: Relevance
“…αSynu cleinimmunoreactive GCIs have been observed in white and grey matter regions, which provide these inputs to the cerebellum in MSA, e.g. the pontocer ebellar and reticulocerebellar tracts [13], and in the present study they were also observed in cerebellar white matter. This pathology has also been observed in motor tracts providing both the input and output pathways of the cerebellum, e.g., the corticopontine, cortical bulbar, corticospinal, and spinoreticular tracts.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…αSynu cleinimmunoreactive GCIs have been observed in white and grey matter regions, which provide these inputs to the cerebellum in MSA, e.g. the pontocer ebellar and reticulocerebellar tracts [13], and in the present study they were also observed in cerebellar white matter. This pathology has also been observed in motor tracts providing both the input and output pathways of the cerebellum, e.g., the corticopontine, cortical bulbar, corticospinal, and spinoreticular tracts.…”
Section: Discussionsupporting
confidence: 77%
“…This pathology has also been observed in motor tracts providing both the input and output pathways of the cerebellum, e.g., the corticopontine, cortical bulbar, corticospinal, and spinoreticular tracts. In addition, significant densities of inclusions have been observed in precerebellar nuclei such as the inferior olivary nucleus [8], lateral reticular nucle us, interfascicular nucleus, and the nucleus of Roller in MSA [13].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with the finding of NPNFP expression in the IOpr and the link between NPNFP expression and the loss of neurons in the cerebral cortex (Hof et al, 1990;Bussiere et al, 2003). Cerebellar or brainstem damage, specifically to the central tegmental tract, results in a specific type of degeneration in the olive, ''hypertrophic olivary degeneration,'' (Weber, 1942;Gautier and Blackwood, 1961;Goto et al, 1988;Braak et al, 2003;Rü b et al, 2005;Aladdin et al, 2008;Valente et al, 2008). There is also degeneration of IO neurons in several neurological disorders, for example spinocerebellar ataxias and Joubert syndrome (Braak et al, 2003;Rü b et al, 2005;Valente et al, 2008;Popescu et al, 2009).…”
Section: Structure Of the Human Ioprmentioning
confidence: 99%
“…The brains were fixed in 10% formalin, embedded either in paraffin or celloidin, serially sectioned coronally at a thickness of 20 or 30 m and stained for cells (cresyl violet), fibers (Heidenhain-Woelcke), or impregnated with protargol silver stain (Bodian), respectively [Dailly, 1972;Schwerdtfeger et al, 1984]. These slides were compared to a microslide control series of the human brainstem cut at a thickness of 100 m and stained with aldehydefuchsin-Darrow red from the control case collection of the Dr. Senckenbergische Anatomie, Frankfurt a.M. [Braak et al, 2003]. The control individual was without any record of neuropsychiatric diseases.…”
Section: Methodsmentioning
confidence: 99%